Morfometri Limpa Berkaitan dengan Produksi Radikal Bebas dan Antioksidan pada Kelelawar Pemakan Buah Codot Krawar (Cynopterus brachyotis) - Hanadhita, Desrayni; Prawira, Andhika Yudha; Rahma, Anisa; Satyaningtijas, Aryani Sismin; Agungpriyono, Srihadi (Jurnal Veteriner; Vol 19 No 1 (2018), 2018)
Fruit bats have been reported as the natural reservoir of many emerging and re-emerging zoonotic diseases. Infected bats usually do not show any clinical symptoms and are infected persistently. This unique characters indicate that bats have high immune activity to combat viruses even in its physiological state. High immune activity will affect the size of lymphoid organ and produce high level of reactive oxygen species (ROS). Spleen is one of the important lymphoid organ which have a strategic function in elimination of blood borne pathogens. This study was undertaken to provide information on the normal size of spleen and to analyze malonaldehyde (MDA) and super oxide dismutase (SOD) levels of free range fruit bats (Cynopterus brachyotis). The ratio of body weight/spleen was 0.4% and there were no significance differences between the male and female bats. The spleen MDA levels which represent ROS generation was higher than those of the liver. Male bats with higher levels of MDA tend to have bigger spleen size than the female which has lower MDA levels. High levels of MDA might indicate a high immune activity inside the spleen. Despite the negative effect of ROS to genetic material, high level of ROS can be advantageous to support the bats immune system as a viral reservoir. High levels of MDA are generally accompanied by high levels of SOD which might reduce the negative impact of oxidative stress in the C. brachyotis.